Taxonomy and Multi-Gene Phylogeny of Poroid Panellus (Mycenaceae, Agaricales) With the Description of Five New Species From China - Zhang, Qiu-Yue; Liu, Hong-Gao; Papp, Viktor; Zhou, Meng; Wu, Fang; Dai, Yu-Cheng (Frontiers in Microbiology, 2022)
Panellus is an Agaricales genus with both lamellate and poroid hymenophore. The poroid species are readily overlooked because of their tiny basidiocarps. The Chinese samples of poroid Panellus are studied, and five species, namely Panellus alpinus, Panellus crassiporus, Panellus longistipitatus, Panellus minutissimus, and Panellus palmicola are described as new species based on morphology and molecular phylogenetic analyses inferred from an nrITS dataset and a multi-gene dataset (nrITS + nrLSU + mtSSU + nrSSU + tef1). Panellus alpinus is characterized by its round to ellipsoid pores measuring 4–6 per mm and oblong ellipsoid basidiospores measuring 4.8–6 μm × 2.8–3.6 μm; P. crassiporus differs from other poroid species in the genus by the irregular pores with thick dissepiments and globose basidiospores measuring 8–9.8 μm × 6.9–8 μm; P. longistipitatus is distinguished by its long stipes, pyriform cheilocystidia, and broadly ellipsoid to subglobose basidiospores measuring 7–9.8 μm × 5–7 μm; P. minutissimus is characterized by its tiny and gelatinous basidiocarps, 5–20 pores per basidiocarp, and ellipsoid basidiospores measuring 6–8 μm × 3.2–4.2 μm; P. palmicola is characterized by its round pores measuring 2–4 per mm, the presence of acerose basidioles, and globose basidiospores measuring 7–9.5 μm × 6.2–8.2 μm. An identification key to 20 poroid species of Panellus is provided.